Efficacy of Dexmedetomidine as Adjuvant to Ropivacaine in Supraclavicular Brachial Plexus Block for Upper Limb Surgery. - Shah, Parasmani; Bhattarai, Rupak; Sarraf, Supriya (Birat Journal of Health Sciences, 2025)
Introduction: Use of ropivacaine alone in brachial plexus block can provide dense anaesthesia of upper limb for shorter duration and have shorter period of postoperative analgesia. However, many drugs are being used as an adjuvant to local anaesthetic to enhance onset, efficacy and duration of anaesthesia and postoperative analgesia. Objectives: The main objective of our study is to assess the efficacy of dexmedetomidine as an adjuvant to ropivacaine for supraclavicular brachial plexus block. Methodology: This is a prospective comparative study conducted on 60 patients aged between 18 to 65 years undergoing below elbow upper limb surgery under brachial plexus block. Patients were equally divided into two groups. Group R patients received 25 ml of 0.5% ropivacaine with normal saline (2 ml) whereas Group D patients received 25 ml of 0.5% ropivacaine with 1mcg/kg dexmedetomidine (2 ml). The time of onset and duration of sensory and motor block and duration of analgesia were compared among groups. Results: Demographic variables were comparable in both groups. There was faster onset and longer duration of sensory and motor block in group D than that in group R. Duration of analgesia was shorter in group R compared to group D. Conclusion: Use of dexmedetomidine as adjuvant to ropivacaine in supraclavicular brachial plexus block hastens the time to onset and prolongs the duration of anaesthesia and postoperative analgesia.